2009
DOI: 10.1063/1.3114405
|View full text |Cite
|
Sign up to set email alerts
|

Fiber-coupled surface-emitting photonic crystal band edge laser for biochemical sensor applications

Abstract: We report on a refractive index sensor platform based on a surface-emitting photonic crystal (PC) Γ-point band edge laser (BEL). A simple butt-end fiber coupling makes the BEL system compact, while the translational symmetry of the PC pattern removes the necessity of fiber alignment. The laser wavelength shifts linearly to longer wavelengths as the refractive index of the environmental medium increases. Our BEL system had an index resolution of ∼10−3. Taking into account the alignment-free nature, as well as i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 18 publications
1
43
1
Order By: Relevance
“…Silicon based PhC microcavities have been used to detect (bio) chemical complexes [12][13][14]19]. Sensors based on III-V semiconductors have been demonstrated as well [11,15,17]. These latter sensors are attractive as they potentially offer the full on-chip integration with sources and detectors, or may be operated as lasers [15] to decrease the detection level.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Silicon based PhC microcavities have been used to detect (bio) chemical complexes [12][13][14]19]. Sensors based on III-V semiconductors have been demonstrated as well [11,15,17]. These latter sensors are attractive as they potentially offer the full on-chip integration with sources and detectors, or may be operated as lasers [15] to decrease the detection level.…”
Section: Introductionmentioning
confidence: 99%
“…Many efforts exist to realize small devices and among them are photonic crystal (PhC) fibers [9], microrings [6,10] and PhC cavities [11][12][13][14][15][16][17][18][19]. The smallest possible sensors are the ones based on PhC cavities as their size is of the order of the wavelength, determined by the diffraction limit.…”
Section: Introductionmentioning
confidence: 99%
“…Also higher order of sensing parameters can be achieved by this rhombic ring resonator such as resonant wavelength is in the range of 1540-1560nm, quality factor is of 178.6, 100% of transmission efficiency and sensitivity is of 1000nm/RIU. Hence the higher orders of sensing parameters are achieved in this paper which is greater than literatures reported before [14,22,[15][16][17][18][19][20][21]. The rest of the paper is organized as follows, the proposed design is explained in section 2, simulation results and discussions are reported in section 3 and section 4 concludes the paper.…”
Section: Introductionmentioning
confidence: 91%
“…Further Kim et al have reported the design of surface emitting photonic crystal with point band edge laser to investigate the performances of different refractive indices of liquids from 1.296-1.372 with span of 0.019. Thereby the sensitivity is getting improved as 135nm/RIU [18]. Moreover, in 2014, Najafgholinezhad and Olyaee have done an investigation on photonic crystal with microcavity resonator for analysis over the temperature dependency of water.…”
Section: Introductionmentioning
confidence: 99%
“…Since the cavities are luminescent, they can be read out remotely in free space using either objectives or fiber-optic components. 23 They can, thus, be employed as autonomous particles that perform a variety of useful functions when transferred to a foreign substrate. Examples include the function as sensors, for example, refractive index or temperature, either when attached to a foreign surface or when suspended in a liquid as a spectrum-encoded particle.…”
Section: Discussionmentioning
confidence: 99%